Multimodal Discourse Analysis Kim Jong-Hyun’s Suicide Report from South Korea and United Kingdom’s Online Articles - Sonia, Hanifa Az Zahrawaanis; Harti, Laily Maulida Septiana (New Language Dimensions, 2022)
This study reports a Multimodal Discourse Analysis of thirteen English-language online articles from South Korea’s and the United Kingdom’s news media reporting Kim Jong-Hyun’s suicide on 18th - 19th December 2017. This qualitative study refers to Halliday’s ideational metafunction and Kress & van Leeuwen’s representational meaning. This study is limited to analyzing online articles’ headlines and lead images to find how news media from South Korea and the United Kingdom differ in reporting Kim Jong-Hyun's suicide. Upon the analysis, both South Korea’s and the United Kingdom’s news headlines are mostly employing material processes. Yet, South Korea’s news headline is not only written about Kim Jong-Hyun’s death but also the impact on society. Meanwhile, the United Kingdom’s news headlines provide more information about the reason background of why Kim Jong-Hyun took his own life. Also, within the representational meaning analysis, it is found that South Korea’s lead images are more variative especially when its lead image combines narrative and conceptual processes compared to United Kingdom’s lead image which is more general and more or less stable and timeless essence. This study is also significant to the discourse of suicide news reports which is rarely analyzed.